2019
DOI: 10.31234/osf.io/wskd4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The boss is not always right: Norwegian preschoolers do not selectively endorse the testimony of a novel dominant agent

Abstract: Children are selective cultural learners, and they rely heavily on social cues when determiningwhom to trust in the face of conflicting information. Although theories of cultural evolution predict that prestige, rather than dominance, cues should guide culturally-transmitted learning, preschoolers in two cross-culturally diverse samples were recently reported to selectively endorse the claims of a socially dominant agent. Here we show, however, that preschoolers in Norway, a highly egalitarian culture, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Finally, our results also differ from those on testimony. Indeed, while in Norway and Japan preschool children did not believe the testimony of a dominant character more (Charafeddine et al, 2019;Fonn et al, 2019), French participants comparable to the current groups of participants did (Bernard et al, 2016). This suggests that high-power individuals influence children's representation of objective questions more than their desires and aspirations.…”
Section: No Overall Influence Of the High-power Charactermentioning
confidence: 51%
See 3 more Smart Citations
“…Finally, our results also differ from those on testimony. Indeed, while in Norway and Japan preschool children did not believe the testimony of a dominant character more (Charafeddine et al, 2019;Fonn et al, 2019), French participants comparable to the current groups of participants did (Bernard et al, 2016). This suggests that high-power individuals influence children's representation of objective questions more than their desires and aspirations.…”
Section: No Overall Influence Of the High-power Charactermentioning
confidence: 51%
“…Preschool children endorsed the statements of the dominant character more than those of the subordinate character (see also Castelain et al, 2016). However, this effect was not replicated with children living in a more egalitarian culture, such as Norway (Fonn et al, 2019), and in Japan, a culture that places high value on modesty and subordination, preschool children have even been found to believe the testimony of the subordinate character more than that of the dominant character (Charafeddine et al, 2019).…”
Section: The Evaluation Of Powerful Othersmentioning
confidence: 98%
See 2 more Smart Citations
“…Another small set of studies investigated the relation between children's understanding of social dominance and their decisions to allocate trust, reporting mixed results here too: Two studies found that preschoolers trusted dominants (with either physical or decisional power) over subordinates [26,27], but a third work found that children were equally likely to choose dominants and subordinates [28]. Finally, while a few studies looked at whether children selectively trust dominants vs. subordinates, no prior study investigated whether children trust different types of dominants, e.g.…”
Section: Introductionmentioning
confidence: 99%